Acute Effects of Intra-Coronary Tirofiban on No-Reflow Phenomena in Patients with ST-Segment Elevated Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention - Zahid, Zonish; Abdul Majid; Rasool, Abbas (Indus Journal of Bioscience Research, 2025)
Background: No-reflow phenomenon following primary percutaneous coronary intervention in ST-segment elevation myocardial infarction increases mortality risk. Intracoronary tirofiban has shown variable results in previous studies, with success rates ranging from 0% to 96.7%. This study aimed to determine the acute effects of intracoronary tirofiban in patients with persistent no-reflow despite intracoronary nitroglycerine administration. Methods: This quasi-experimental study included 131 patients aged 30-75 years with ST-segment elevation myocardial infarction who developed no-reflow phenomenon (TIMI grade 0) during primary percutaneous coronary intervention at Sheikh Zayed Medical College and Hospital, Rahim Yar Khan, from 25-February to 24-June 2025. Following failed response to intracoronary nitroglycerine, intracoronary tirofiban was administered at 25 μg/kg. Coronary angiography was repeated after ten minutes to assess TIMI flow grade improvement. Data analysis included descriptive statistics and stratified analysis using chi-square test, with statistical significance set at p ≤ 0.05. Results: The mean age was 56.3 ± 10.8 years, with 71.8% male patients. TIMI grade 3 flow was achieved in 82.4% of patients (95% CI: 75.3%-88.2%). Overall improvement in TIMI flow was observed in 87.8% of cases. Statistically significant associations were found between TIMI grade 3 achievement and age groups (p=0.048), body mass index categories (p=0.041), infarction territory (p=0.019), diabetes mellitus (p=0.024), and smoking status (p=0.026). Conclusion: Intracoronary tirofiban demonstrated substantial efficacy in reversing no-reflow phenomenon after failed nitroglycerine therapy, with higher success rates in younger patients, non-diabetic individuals, non-smokers, and those with inferior wall infarction.